Multidisciplinary Management of Breast Cancer During Pregnancy. (23rd February 2017) - Shachar, Shlomit Strulov; Gallagher, Kristalyn; McGuire, Kandace; Zagar, Timothy M.; Faso, Aimee; Muss, Hyman B.; Sweeting, Raeshall; Anders, Carey K.
Abstract: Background: Although breast cancer during pregnancy (BCDP) is rare (occurring with only 0.4% of all BC diagnoses in female patients aged 16–49 years), management decisions are challenging to both the patient and the multidisciplinary team. Materials and Methods: Experts in breast cancer at the University of North Carolina conducted a targeted literature search regarding the multidisciplinary treatment approaches to BCDP: medical, surgical, and radiation oncology. Supportive care, including antiemetic agents, and imaging approaches were also reviewed. Results: Review of the literature revealed key points in the management of BCDP. Surgical management is similar to that in nonpregnant patients; pregnant patients may safely undergo breast‐conserving surgery. Recommendations should be tailored to the individual according to the clinical stage, tumor biology, genetic status, gestational age, and personal preferences. Anthracycline‐based chemotherapy can be safely initiated only in the second and third trimesters. The rate of congenital abnormalities in children exposed to chemotherapy is similar to the national average (approximately 3%). Dosing of chemotherapy should be similar to that in the nonpregnant patient (i.e., actual body surface area). Antihuman epidermal growth factor receptor 2 therapy, radiation, and endocrine treatment are contraindicated in pregnancy and lactation. Care should include partnership with obstetricians. The literature regarding prognosis of BCDP is mixed. Conclusion: To maximize benefit and minimize risk to the mother and fetus, an informed discussion with the patient and her medical team should result in an individualized treatment plan, taking into account the timing of the pregnancy and the stage and subtype of the breast cancer. Because BCDP is rare, it is essential to collect patient data in international registries. Implications for Practice: Breast cancer during pregnancy is a major ethical and professional challenge for both the patient and the multidisciplinary treatment team. Although the oncologic care is based on that of the non‐pregnant breast cancer patient, there are many challenges from regarding the medical, surgical and radiation oncology and obstetrical aspects of care that need to be considered to deliver the safest and best treatment plan to both the mother and developing fetus. Abstract : This article provides evidence‐based, practical guidance to the optimal approach and treatment of patients diagnosed with breast cancer during pregnancy.